A STUDY ON THE ERRORS MADE BY THE FIFTH SEMESTER STUDENTS OF THE ENGLISH DEPARTMENT OF UNIVERSITAS RIAU IN USING CONDITIONAL SENTENCES - Nadya Eka Putri; Supriusman Supriusman; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out the type of conditional sentences the fifth-semester students of the English Department of Universitas Riau make errors. The population was the fifth-semester students of The English Department at Teachers Training and Education Universitas Riau, they consisted of three classes: class A, class B, and class C. From 114 students of the population, the participant was taken as the sample of this research consists of 30 students. Purposive sampling was used to choose the sample. The instrument used written test in which students must use the word in the bracket into the correct type of Conditional Sentences. In analyzing the data, it had been done by calculating the scores of students individually and looking for the mean scores. Based on the result, it was found that the errors made by the fifth semester students of the English department of Universitas Riau in using conditional sentences is in using conditional sentences type 1, the students made 115 errors (22.8%). In type 2 students made 136 errors (27%). In type 3 students made 253 errors (50.2%). The students made 504 errors in conditional sentences type 1, 2 and 3. Conditional sentences type 3 becomes the highest error that students made. The second highest errors made by students were in using conditional sentences type 2, while the lowest errors made by students were in using conditional sentences type 1. Based on this result, it is suggested for the students should pay more attention in learning and teaching process. The students should have more practice in grammar and remember the grammatical pattern and rules. As for the lecturers, it is better to explain as clear as possible all of the types of conditional sentences generally and conditional sentences type 3 specifically, not only the meaning and formula but also the usage.Key Words: Conditional Sentences, Error, Students